Global trends in research of glutamate in epilepsy during past two decades: A bibliometric analysis - Wang, Wei; Gao, Runshi; Ren, Zhiwei; Yang, Dongju; Sun, Ke; Li, Xiaoling; Yan, Suying (Frontiers in Neuroscience, 2022)
Epilepsy affects more than 70 million people in the world. It is characterized by recurrent spontaneous seizures, and it is related to many neurological, cognitive, and psychosocial consequences. Glutamate neurotransmitter dysfunction has essential functions in the pathophysiology of epilepsy. In this work, bibliometric analysis was conducted to explore the trends, frontiers, and hotspots of the global scientific output of glutamate in epilepsy research in the past 20 years. The Science Citation Index Expanded of the Web of Science Core Collection (WoSCC) was searched to obtain information on publications and records published between 2002 and 2021. VOSviewer and CiteSpace were used to conduct bibliometric and visual analyses on the overall distribution of annual output, major countries, active institutions, journals, authors, commonly cited literature, and keywords. The impact and quality of the papers were assessed using the global citation score (GCS). Four thousand eight hundred ninety-one publications were retrieved in total. During the past two decades, the number of publications (Np) associated with glutamate in epilepsy has risen yearly. The United States has published the most papers; its H-index and number of citations are also the highest. The League of European Research Universities (LERU) was the most productive institution. In 2016, the total score of the paper written by Zhang Y was 854, ranking first. The keywords that appear most frequently are “epilepsy,” “glutamate,” “temporal lobe epilepsy (TLE),” “hippocampus,” and “seizures.” This study showed that although the publications related to epileptic glutamate fluctuated slightly, the Np increased overall. The United States is a great creator and influential country in this field. The first three authors are Eid, T., Aronica, E., and Smolders, I. “spectrum,” “animal model,” “inflammation,” “mutation,” “dysfunction,” and “prefrontal cortex” are increasing research hotspots. By recognizing the most critical indicators (researchers, countries, research institutes, and journals of glutamate release in epilepsy research), the research hotspot of glutamate in epilepsy could help countries, scholars, and policymakers in this field enhance their understanding of the role of glutamate in epilepsy and make decisions.